2019
DOI: 10.1371/journal.pone.0221036
|View full text |Cite
|
Sign up to set email alerts
|

Brain-related proteins as serum biomarkers of acute, subconcussive blast overpressure exposure: A cohort study of military personnel

Abstract: Repeated exposure to blast overpressure remains a major cause of adverse health for military personnel who, as a consequence, are at a higher risk for neurodegenerative disease and suicide. Acute, early tracking of blast related effects holds the promise of rapid health assessment prior to onset of chronic problems. Current techniques used to determine blastrelated effects rely upon reporting of symptomology similar to that of concussion and neurocognitive assessment relevant to operational decrement. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 55 publications
(57 reference statements)
3
26
0
Order By: Relevance
“…This time-dependent observation is often overlooked and may indicate that acute (e.g., hourly) temporal dynamics of Nf-L may be useful in monitoring early phase OP-mediated effects when compared to a participant's basal biomarker levels, whereas leakage of a fairly large protein from the CNS is useful in the context of a known variable (e.g., clinical TBI diagnosis) during longer timeframes (e.g., weeks-months). Our group has previously reported that serum GFAP levels also decreased in accordance with persistent concussion-like symptomology after mild-to-moderate OP exposure caused by blast (34). Replication of both observations with larger cohorts and variation of peak OP levels and assessment of medical relevance compared to basal levels is ongoing.…”
Section: Discussionmentioning
confidence: 65%
“…This time-dependent observation is often overlooked and may indicate that acute (e.g., hourly) temporal dynamics of Nf-L may be useful in monitoring early phase OP-mediated effects when compared to a participant's basal biomarker levels, whereas leakage of a fairly large protein from the CNS is useful in the context of a known variable (e.g., clinical TBI diagnosis) during longer timeframes (e.g., weeks-months). Our group has previously reported that serum GFAP levels also decreased in accordance with persistent concussion-like symptomology after mild-to-moderate OP exposure caused by blast (34). Replication of both observations with larger cohorts and variation of peak OP levels and assessment of medical relevance compared to basal levels is ongoing.…”
Section: Discussionmentioning
confidence: 65%
“…Severe traumatic brain injury (TBI) remains a significant health issue that leads to cognitive and physical impairment, prolonged hospitalization, and the need for long-term care (Langlois et al, 2005;Zaloshnja et al, 2008;Cuthbert et al, 2015;Taylor et al, 2017). Military personnel are at a particularly high risk for encountering a TBI (Santiago et al, 2012) due, in part, to improvised explosive devices and munition exposures (Meyer et al, 2010;Boutte et al, 2019). Patients who suffer from a TBI are at a much higher risk of developing neurodegenerative disease or dementia (Plassman et al, 2000), particularly Alzheimer's disease (AD) (Mendez et al, 2015), Parkinson's disease (PD) (Gardner et al, 2018), Amyotrophic lateral sclerosis (ALS) (Franz et al, 2019), psychological disorders (Veitch et al, 2013), post-traumatic stress disorder (PTSD) (Friedemann-Sanchez et al, 2008), and suicide (Goldstein and Diaz-Arrastia, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The blast wave propagation inside combat helmets is a complex problem, with the pressure focusing under the helmet dependent on several factors: 1) the shape of the helmet; 2) orientation relative to the source of the blast wave, and 3) the suspension system (i.e., number of pads, their distribution under the helmet and material properties). The mounting evidence suggests an association between occupational low-level blast exposure and acute adverse neurological effects [26], and related serum biomarkers changes [27,28]. The role of the helmet in the development of these effects is unclear at this time.…”
Section: Introductionmentioning
confidence: 99%